Exercise Training Improves Whole Body Insulin Resistance via Adiponectin Receptor 1 - Cho, J.-K.; Kim, S.-U.; Hong, H.-R.; Yoon, J.-H.; Kang, H.-S. (International Journal of Sports Medicine, 2015)
Little is known regarding whether adiponectin receptors mediate high-intensity interval training (HIT)-induced improvement of insulin resistance associated with obesity. This study investigated the effect of HIT on whole body insulin resistance in high-fat diet-induced obese mice. 5-week-old male mice (N=30) were randomly assigned to standard chow (SC) (n=10) or HFD (n=20) for 23 weeks. After 15 weeks of dietary treatment, the HFD mice were further assigned to HFD (n=10) or HFD plus HIT (HFD+HIT, n=10). The HFD+HIT mice were subjected to HIT during the last 8 weeks of the 23-week HFD course. HFD resulted in whole body insulin resistance, hypoadiponectinemia, suppressed expression of adiponectin receptor 1(AdipoR1) and 2 (AdipoR2), suppressed expression of phosphorylated AMP-activated protein kinase (p-AMPK) and NAD-dependent deacetylase sirtuin-1 (SIRT1), and decreased mRNAs of peroxisome proliferator-activated receptor-α (PPARα), carnitine palmitoyltransferase I (CPT1), and acyl CoA oxidase (ACO) in skeletal muscle. In contrast, HIT alleviated whole body insulin resistance and prevented decreased levels of total adiponectin in both serum and adipose tissue. HIT also prevented the down-regulation of AdipoR1 and AMPK/SIRT1 proteins and the down-regulation of PPARα, CPT1, and ACO mRNAs. The current findings show that HIT alleviates whole body insulin resistance due to HFD-induced obesity via the AdipoR1 and AMPK/SIRT1 mediated-signaling pathway in skeletal muscle, implying the potential role of HIT to combat this metabolic condition.
Keywords: exercise training; skeletal muscle; hypoadiponectinemia; metabolic disorders